The Litex Market and Park Complex a reimagined community market scene - Ardon, Francheska C.
The Batasan-NGC Growth Center, at present, is a community of urban poor that is much bigger than the other cities in Metro Manila. In order to support their daily needs and expenses, small scale commercial activities have emerged and are continually increasing as the needs and population also increases. The number of sufficient land areas to cater for these commercial activities could not keep up with this demand, thus, the vendors tend to invade public spaces instead. However, the number of public spaces around the growth center is limited, providing less open spaces for the community to use to create better and more appropriate design solutions, the project aims to explore how architecture can serve as a venue for quality economic growth while protecting and enriching the welfare of the community. With this, the project is the redevelopment of the existing Litex markets into a community-based commercial, institutional, and recreational complex. Through the reimagining of a community market and park, the Litex Market and Park Complex not only uplifts the economic conditions of its vendors but also strengthens the community it serves. Through site-specific and community-based design, the project shall show how markets and parks can be integrated to successfully provide for and adapt to its community's needs.